INCIDENTAL VOCABULARY ACQUISITION THROUGH VIEWING L2 TELEVISION AND FACTORS THAT AFFECT LEARNING - Peters, Elke; Webb, Stuart (Studies in second language acquisition, 2018)
Research has begun to demonstrate that L2 words can be learned incidentally through watching audio-visual materials. Although there are a large number of studies that have investigated incidental vocabulary learning through reading a single text, there are no studies that have explored incidental vocabulary learning through viewing a single full-length TV program. The present study fills this gap. Additionally, three word-related variables (frequency of occurrence, cognateness, word relevance) and one learner-related variable (prior vocabulary knowledge) that might contribute to incidental vocabulary learning were examined. Two experiments were conducted with Dutch-speaking EFL learners to measure the effects of viewing TV on form recognition and meaning recall (Experiment 1) and meaning recognition (Experiment 2). The findings showed that viewing TV resulted in incidental vocabulary learning at the level of meaning recall and meaning recognition. The research also revealed that learning was affected by frequency of occurrence, prior vocabulary knowledge, and cognateness.